2022
DOI: 10.4314/sa.v21i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating potential of aluminum sulphate (alum) on testosterone propionate-induced benign prostatic hyperplasia in male Wistar rats

Abstract: The effect of aluminum sulphate (alum) on Testosterone propionate (TP)-induced Benign Prostatic Hyperplasia (BPH) in male Wistar rats was studied. Eighty mature male Wistar rats, with an average weight of 210g, were randomly distributed into eight groups comprising ten rats. Group 1 received only food and water, while Groups 2, and 4 to 8 were given 3 mg/kg b.w of TP subcutaneously and Group 3 received only 25 % alum solution for 28 days. Thereafter, Groups 4 to 8 were treated with 10%, 20%, 25%, 30%, and 40% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Furthermore, ELAM significantly increased the FSH levels in the ameliorative and protective phase, which has its physiology linked to combating ROS formation attached to the flavonoids and saponins. Onyegeme-Okerenta et al(126) and Olowofolahan et al(127) reported a significant decline in FSH level following Annona muricata in reproductive dysfunction, which disagree with the study outcome. The study corroborates the findings of Abd El-Monem and Elwakeel(128) and El-Sawi et al(129), revealing a significantly higher level of FSH following Annona muricata extract against testicular toxicity.…”
mentioning
confidence: 67%
“…Furthermore, ELAM significantly increased the FSH levels in the ameliorative and protective phase, which has its physiology linked to combating ROS formation attached to the flavonoids and saponins. Onyegeme-Okerenta et al(126) and Olowofolahan et al(127) reported a significant decline in FSH level following Annona muricata in reproductive dysfunction, which disagree with the study outcome. The study corroborates the findings of Abd El-Monem and Elwakeel(128) and El-Sawi et al(129), revealing a significantly higher level of FSH following Annona muricata extract against testicular toxicity.…”
mentioning
confidence: 67%
“…The dried extract was weighed and stored in a clean reagent bottle, then preserved in a refrigerator at 4 O C before use. 22 Experimental design Forty-eight adult female Wistar rats with an average weight of 186 g were bought from animal breeders and kept in the Department of Biochemistry, University of Port Harcourt Animal house. The rats were allowed to get acclimatized to the environment for one week and had unrestricted access to normal rat chow and water ad libitum.…”
Section: Collection and Identification Of Specimensmentioning
confidence: 99%
“…Numerous health benefits 20 have been attributed to A. muricata, most of which has been linked to its antioxidant potential. 21,22 This study was carried out to ascertain the effect of prolonged dose of chloramphenicol on the erythropoietic processes and its cytotoxic potential in inducing leukaemia and the modulatory prospective of aqueous leaf extract of A. muricata on CIL in female Wistar rats.…”
Section: Introductionmentioning
confidence: 99%